Effect of thermo mechanical stimulation during local anesthesia in pediatric dentistry: a pilot randomized clinical trial - Fernanda Vieira Almeida; Bruna Martins da Silva; Edde Caroline Menezes diGesu; Andréia Drawanz Hartwig; Ivam Freire da Silva Júnior; Marília Leão Goettems (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2023)
Aim: To evaluate the effectiveness of a thermo mechanical stimulation device (Buzzy®) in relation to pain, fear and anxiety during local anesthesia in children. Materials and methods: Study carried out from May 2018 to July 2019, with children aged 7 to 11 years, without previous experience involving anesthesia in the last 2 years and who needed dental treatment (extraction, restoration or endodontic) under local anesthesia in deciduous molars. The sample was randomized into a control group, which received conventional anesthesia, and an intervention group, which received anesthesia with Buzzy®. The levels of anxiety, fear and pain perception of both groups were verified using: Come Modified Picture Test (VPTM); heart rate; Behavioral Scale Come; Faces Pain Scale - Revised (FPS-R) and Face, Legs, Activity, Cry, Consolability (FLACC). Results: Most children (55%) had low anxiety before and after treatment (P<0.05). The acceptability of the children to Buzzy® was 100% and the majority (90%) would like to use it again. Discussion: The tested device is an interesting tool to complement management techniques during consultations, in view of the excellent acceptability and interest on the part of patients and family members. Conclusion: This study demonstrated that the use of thermo mechanical stimulation is feasible in the dental clinic, due to its easy use and good acceptability in the clinical environment, in addition to not presenting risks in its use.